Intra-operative cutaneous temperature monitoring with zero-heat-flux technique (3M SpotOn) in comparison with oesophageal and arterial temperature: A prospective observational study. Issue 11 (November 2018) - Boisson, Matthieu; Alaux, Anouk; Kerforne, Thomas; Mimoz, Olivier; Debaene, Bertrand; Dahyot-Fizelier, Claire; Frasca, Denis
Abstract : BACKGROUND: Continuous monitoring of core temperature is essential during major surgery as a way of improving patient safety. Oesophageal probes or specific arterial catheters are invasive methods used in this setting. A new noninvasive device based on zero-heat-flux (ZHF) technique (SpotOn) seems promising but has been poorly investigated during rapid core temperature changes (RCTC). OBJECTIVE: To assess the accuracy of a SpotOn sensor vs. an oesophageal probe or specific arterial catheter during a slow change in core temperature of less than 1 °C within 30 min and RCTC ≥ 1 °C within 30 min. DESIGN: Prospective observational study. SETTING: Operating rooms at the University Hospital of Poitiers, France. PATIENTS: Fifty patients scheduled for major abdominal surgery under general anaesthesia were enrolled from June 2015 to March 2016. Data from 49 patients were finally analysed. Among these, 15 patients were treated with hyperthermic intraperitoneal chemotherapy. INTERVENTION: Each patient had a ZHF sensor placed on the skin surface of the forehead (TempZHF ) and an oesophageal probe (TempEso ) used as a reference method. Twenty-two patients also had a thermodilution arterial catheter (TempArt ) placed in the axillary artery. MAIN OUTCOME MEASURES: Core temperature was continuously recorded from the three devices after induction of anaesthesia. Comparison of temperature measurements between methods was made using the Bland and Altman method during two separate periods according to the speed of core temperature changes. RESULTS: Compared with TempEso, bias and limits of agreement for TempZHF were 0.1 ± 0.5 °C during slow core temperature changes periods and 0.6 ± 1.8 °C during RCTC periods ( P = 0.0002). Compared with TempArt, these values were −0.1 ± 0.4 and 0.5 ± 1.7 °C, respectively ( P = 0.0039). The ZHF sensor was well tolerated. CONCLUSION: A SpotOn sensor using the ZHF method seems reliable for core temperature monitoring during abdominal surgery when variations in core temperature are slow rather than rapid. TRIAL REGISTRATION: ClinicalTrials.gov identifier: NCT02869828.